GP259 Fresh or frozen: what is the difference?. (June 2019) - Tabassum, Saira; Conlon, Emma; O'Connor, Pamela; O'Sullivan, Anne; McCartney, Daniel; White, Martin; Dunlevy, Fiona; Doolan, Anne
Abstract : Background: Maternal expressed breast milk is the feed of choice for the preterm infant who is unable to latch to feed. Most mothers express and store milk in the fridge or freezer for later use. Irish Breast feeding guidelines recommends storage of fridge freezer for 3 months and deep freezer for 6 months. 1 Some reports suggest no change in macronutrient content after freezing up to 3 months while others report a decrease in fat and caloric content of breast milk. 2 Aim: To compare the difference in macronutrient content between paired fresh and frozen maternal expressed breast milk samples. Methods: A total of 20 pooled expressed breast milk samples were collected from 15 mothers, expressing for their preterm infants with mean gestation at birth = 28.3 weeks. Mean infants birth weight was 1143 (±364) grams. As per local hospital policy samples were frozen at -25°C within 24 hours of expression. Breast milk samples were analysed by human milk analyser (MIRIS®) after ultrasonic homogenization after thawing in room-air and warming to 40°C. Results: Median time of freezing was 33 (7–70) days. Macro-nutrient composition varied (as shown in table 2 ), with fat and caloric content most effected. Some loss of protein content was observed. Discussion: Our study shows a decrease in fat and energy content of maternal expressed breast when frozen. This should be taken into consideration when using frozen expressed breast milk for preterm infants and fresh breast milk used where feasible. References: www.Breastfeeding.ie/factsheet/ Garcia-Lara NR, Escuder-Vieco D, Garcia-Algar O, De la Cruz J, Lora D, Pallas-Alonso C. Effect of freezing time on macronutrients and energy content of breastmilk. Breastfeed Med . 2012;7:295–301. Ahrabi AF, Handa D, Codipilly CN, Shah S, Williams JE, McGuire MA, et al. Effects of Extended Freezer Storage on the Integrity of Human Milk. The Journal of pediatrics . 2016;177:140–3.